Femtosecond laser micromachining of advanced materials - Bian, Qiumei (Kansas State University, 2013)
Femtosecond (fs) laser ablation possesses unique characteristics for micromachining, notably non-thermal interaction with materials, high peak intensity, precision and flexibility. In this dissertation, the potential of fs laser ablation for machining polyurea aerogel and scribing thin film solar cell interconnection grooves is studied. In a preliminary background discussion, some key literature regarding the basic physics and mechanisms that govern ultrafast laser pulse interaction with materials and laser micromachining are summarized. First, the fs laser pulses are used to micromachine polyurea aerogel. The experimental results demonstrate that high quality machining surface can be obtained by tuning the laser fluence and beam scanning speed, which provides insights for micromachining polymers with porous structures. Second, a new fs laser micro-drilling technique is developed to drill micro-holes in stainless steel, in which a hollow core fiber is employed to transmit laser pulses to the target position. The coupling efficiency between the laser and the fiber is investigated and found to be strongly related to pulse energy and pulse duration. Third, the fs laser with various energy, pulse durations, and scanning speeds has been utilized to pattern Indium Tin Oxide (ITO) glass for thin film solar cells. The groove width decreases with increasing pulse duration due to the shorter the pulse duration the more effective of the energy used to material removal. In order to fully remove ITO without damaging the glass, the beam scanning speed need to precisely be controlled. Fourth, fs laser has been utilized to scribe Molybdenum thin film on Polyimide (PI) flexible substrate for Copper Indium Gallium Selenide (CIGS) thin film solar cells. The experimental parameters and results including ablation threshold, single- and multiple-pulse ablation shapes and ablation efficiency were discussed in details. In order to utilize the advantages of the fs lasers, the fabrication process has to be optimized for thin film patterning and structuring applications concerning both efﬁciency and quality. A predictive 3D Two Temperature Model (TTM) was proposed to predict ablation characteristics and help to understand the fs laser metal ablation mechanisms. 3D temperature field evolution for both electrons and lattice were demonstrated. The ablation model provides an insight to the physical processes occurring during fs laser excitation of metals. Desired processing fluence and process speed regime can be predicted by calculating the ablation threshold, ablation rate and ablation crater geometry using the developed model.
Keywords: Femtosecond laser; Micromachining; Advanced material; Industrial Engineering (0546); Mechanical Engineering (0548)